Comparison between intensity modulation techniques in the prostate cancer treatment. (September 2016) - Fondelli, S.; Russo, S.; Peruzzi, I.; Barca, R.; Esposito, M.; Leonulli, B. Grilli; Paoletti, L.; Rossi, F.; Alpi, P.; Ghirelli, A.; Pini, S.; Bastiani, P.
Abstract : Introduction: Comparison between VMAT and IMRT, in terms of plan quality is great topic discussion in literature. Purpose: Aim of this work is to assess VMAT dosimetric results compared to IMRT ones on prostate site. Materials and methods: A comparison was made between IMRT and VMAT plans on the first 30 consecutive patients treated with VMAT moderately hypofractionated radiotherapy: 70.2 Gy/26 fractions of 2.7 Gy. IMRT and VMAT plans were elaborated by TPS Elekta Monaco® using a rabiobiological optimization approach. Plans were compared by evaluating D105%, D95%, D93%, D90%, Dmean and D0.5% for the PTV coverage, while for Organs at Risk (OARs), in addition to Dmean and D0.5%, the % of organ receiving 57, 61, 65.8 and 68.4 Gy (rectum), 57, 61, 65.8 and 68.4 (bladder), 35, 39.5 and 43.9 Gy (femoral heads) were considered of interest. Results: Dosimetric analysis shows that PTV coverage is better with VMAT technique and that PTV Dmean is higher than about 1 Gy in VMAT treatments: median value for the PTV Dmean was 70, 6 Gy in VMAT technique vs 69, 7 Gy in IMRT. Regarding OARs sparing, VMAT technique offers a higher sparing of bladder (of about 5% of volume at 57, 61 and 65 Gy) and femoral heads (of about 15% of volume at 30 Gy). Conclusions: Respect to IMRT, VMAT offers higher plan quality with a better PTV coverage. Regarding OARs, VMAT offers higher sparing of bladder and femoral heads. Besides, VMAT is able to provide a considerable reduction in treatment time offering a better delivery efficiency.